1979
DOI: 10.1007/bf00891967
|View full text |Cite
|
Sign up to set email alerts
|

Hairdressers as caregivers. I. A descriptive profile of interpersonal help‐giving involvements

Abstract: The interpersonal help-giving behaviors of 90 hairdressers were explored in depth in an interview study. On the average, hairdressers saw 55 customers a week, and talked 25 minutes with each. About one-third of the talking time concerned clients' moderate to serious personal problems--particularly problems with children, physical health, marriage, depression, and anxiety. Hairdressers reported that offering sympathy and support, being lighthearted, just listening, and presenting alternatives were among their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 4 publications
8
49
0
Order By: Relevance
“…"Some of the most effective supporters may be those who share a context with the person in need" (Albrecht & Adelman, 1984). Those outside of a person's normal circle of contacts, termed "weak links" (Granovetter, 1973), have also been considered support givers (e.g., hairdressers, bartenders, apartment house managers; Cowen et al, 1979;Kelly, 1966;Wiesenfeld & Weiss, 1979). This latter group of individuals are usually public service providers, in a position to offer counsel and advice (Sarason, 1974).…”
Section: Support Providersmentioning
confidence: 98%
See 1 more Smart Citation
“…"Some of the most effective supporters may be those who share a context with the person in need" (Albrecht & Adelman, 1984). Those outside of a person's normal circle of contacts, termed "weak links" (Granovetter, 1973), have also been considered support givers (e.g., hairdressers, bartenders, apartment house managers; Cowen et al, 1979;Kelly, 1966;Wiesenfeld & Weiss, 1979). This latter group of individuals are usually public service providers, in a position to offer counsel and advice (Sarason, 1974).…”
Section: Support Providersmentioning
confidence: 98%
“…Second, supportive messages can serve to enable a distressed person to examine the source of the stress and to present alternative courses of action (Albrecht & A.delman, 1987;Cowen et al, 1979). House (1981) described this as informational support and included in this category advice, suggestions, directives, and technical information.…”
Section: Functionsmentioning
confidence: 98%
“…However, other informal avenues of assistance may be obtained from what Henderson termed "diffuse sources", such as other interpersonal contacts and ties with community organizations. Indeed, as Cowen (1982) noted, "help is where you find it" (p. 385) and his research has examined the extent to which agents such as hairdressers (Cowen, Gesten, Boike, Norton, Wilson, & DeStephano, 1979) or bartenders (Cowen, McKim, & Weissberg, 1981) can serve in this added capacity. Finally, it can be noted that professional sources, such as therapists and counselors, may also be employed by individuals, either to augment or supplement the informal helping source.…”
Section: Sources Of Social Supportmentioning
confidence: 97%
“…regularly occurred between cosmetologists and their clients. Finding support for earlier research that cosmetologists are "natural helpers" (Cowen et al, 1979;Weisenfeld and Weis, 1979), the authors observed that:…”
Section: Occupational Settingsmentioning
confidence: 67%